1983
DOI: 10.1148/radiology.149.2.6622701
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic measurements of the normal liver, spleen, pancreas, and portal vein.

Abstract: Normal values and upper limits (95th percentile) of liver, spleen, pancreas, and portal vein size were determined prospectively with ultrasound in 915 healthy subjects. Sex, age, weight, height, and body surface area were determined in each case. Since correlation of longitudinal and transverse organ diameters with physical data was poor (r less than or equal to 0.3), the authors do not consider it necessary to correct the measurements accordingly. However, the liver is oriented longitudinally in slender subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
103
3
18

Year Published

1988
1988
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(134 citation statements)
references
References 0 publications
10
103
3
18
Order By: Relevance
“…in a study of 915 healthy participants, niederau and colleagues 15 also found similar values; the mean value was 10.5 ± 1.5 on the midclavicular line. in a random sample of 2,080 participants including healthy and ill adults, Kratzer and colleagues 14 found an ultrasonic mean value of 14 ± 1.7 cm on the midclavicular line.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…in a study of 915 healthy participants, niederau and colleagues 15 also found similar values; the mean value was 10.5 ± 1.5 on the midclavicular line. in a random sample of 2,080 participants including healthy and ill adults, Kratzer and colleagues 14 found an ultrasonic mean value of 14 ± 1.7 cm on the midclavicular line.…”
Section: Discussionmentioning
confidence: 58%
“…this is not true in the literature. in a study of 915 healthy adults, niederau and colleagues 15 found a significant difference between genders, but they did not specify the measurement values. in a study of 116 adults, castell 11 concluded that gender is a determining factor for liver size.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Let us point out one limitation of US for this purpose. For instance, the upper borders of the liver and spleen are darkened by the air present in the lower portions of the lungs, and therefore, the limits between liver and spleen and the echogenic line of the lungs images are arbitrarily considered (extrapolated) to be the reference to measure the longitudinal diameters of the organs (Niederau et al 1983).…”
Section: Spleen-mentioning
confidence: 99%
“…This finding is in agreement with our study. However, in their work they used as reference values the sizes of the organs described in 1983 for a Caucasian population, without stratification for height (Niederau et al 1983).…”
Section: Spleen-mentioning
confidence: 99%